Formation of core-shell structure in W-added B4C-based composites. Issue 15 (1st August 2021) - Liu, Yingying; Ge, Sheng; Yihua Huang,; Huang, Zhengren
Abstract: B4 C-TiB2 -SiC composites with W addition were successfully prepared by spark plasma sintering with B4 C, TiB2, SiC, and W as raw materials. The XRD results indicate that the main phases of the composites are B4 C, TiB2, SiC, and W2 B5 . A large number of core-shell structures were observed in the composites with the introduction of W. It is determined that the core is the TiB2 phase and the shell is a (Ti, W) B2 solid solution by EDS, EBSD, and TEM characterization methods. The core-shell structure is conducive to the deflection of cracks, thereby improving the fracture toughness of the composites. As a result, with the increase of W addition from 0 to 5 vol%, the fracture toughness of composites increased from 3.96±0.25 to 5.14±0.23 MPa m 1/2, the Vickers hardness improved from 20.24±0.22 to 28.35±0.22 GPa.